Plazmatické hladiny troponinu T u králíků po podání nových a anineoplastických látek (Oracinu a Dimefluronu) s daunorubicinem - Adamcová, Michaela; Macháčková, Jarmila; Geršl, Vladimír; Hrdina, Radomír; Mazurová, Yvona; Mělka, Milan; Nobilis, Milan (Acta medica. Supplementum, 2001)
Recently, cardiac troponin T (cTnT) has been shown to be a sensitive marker of anthracycline-induced cardiomyopathy. In our study, the cardiotoxicity of repeated i.v. administration (once a week, 10 administrations) of daunorubicin combined with new antineoplastic drugs (with mild side-effects) were followed in two groups of rabbits: 1) Dimefluron (3,9-dimethoxybenfluron hydrochloride-12 mg/kg) + daunorubicin (3 mg/kg), 2) Oracin (6-[2-(2-hydroxyethyl)aminoethyl]-5,11-dioxo-5,6-dihydro-11H- indeno[1,2c]isoquinoline hydrochloride--10 mg/kg) + daunorubicin (3 mg/kg) and compared with the control group (saline--1 ml/kg) and the group with experimentally induced cardiomyopathy (daunorubicin--3 mg/kg). The concentration of cTnT in heparinized plasma samples was measured using commercial kit (Roche). In the control group, plasma levels of cTnT were always within the physiological range (i.e. lower than 0.1 microgram/l) during the experiment. During the development of daunorubicin-induced cardiomyopathy, after the eighth administration of drug, cTnT was significantly higher (0.31 +/- 0.11 microgram/l) in animals with premature deaths compared with the rest of the group (0.04 +/- 0.03 microgram/l). The animals with pathological values of cTnT were at higher risk of premature deaths (P = 0.0006). The combination of daunorubicin either with Oracin or with Dimefluron caused neither significant changes of cTnT levels nor significant deterioration of other followed-up parameters (especially, functional and toxicological parameters). Similarly to the daunorubicin group, the animals with pathological levels of cTnT after the eighth administration of antineoplastic drugs were at higher risk of premature death (P = 0.025). Our results show that the plasma concentration of cardiac troponin T could be a suitable predictive marker of cardiotoxicity of antineoplastic drugs.
Keywords: Animals; biologické markery; Biomarkers; Daunorubicin; zvířata; protinádorová antibiotika; Troponin T; Ethanolamines; Rabbits; troponin T; daunomycin; protokoly protinádorové kombinované chemoterapie; Fluorenes; isochinoliny; králíci; fluoreny; Cardiomyopathies; Isoquinolines; kardiomyopatie; Antibiotics, Antineoplastic; Antineoplastic Combined Chemotherapy Protocols; ethanolaminy